563 VARIATION IN TREATMENT PATTERNS AND OUTCOMES FOR RESECTED ESOPHAGEAL CANCER AT DESIGNATED THORACIC SURGERY CENTERS. (17th September 2021) - Gupta, Vaibhav; Levy, Jordan; Kidane, Biniam; Mahar, Alyson; Ringash, Jolie; Sutradhar, Rinku; Darling, Gail; Coburn, Natalie
Abstract:  : Ontario defined designated thoracic surgery centres to provide high-volume care for patients undergoing esophageal cancer resection. The objective of this study was to compare thoracic centres' performance to non-thoracic centres, and to assess variation in treatment patterns and outcomes across thoracic centres. Methods: A retrospective cohort study (2002–2014) was conducted in Ontario, Canada (population 13.6 million), examining adults with resected esophageal cancer. Case mix, use of neoadjuvant therapy, surgical outcomes (lymph node yield and positive margin rates) and survival were described across the 15 thoracic centres. Multivariable regression was used to estimate the effect of having surgery at designated thoracic centres on postoperative (in-hospital & 90-day post-discharge) mortality and overall survival, adjusting for case mix. Results: Of 3, 880 patients meeting study criteria, 2, 213 had pathology data available and were included in the analysis. Average age was 64 years, 85.7% had adenocarcinoma, 50.2% were pT3, and 38.4% were pN0. Patients at thoracic centres (82.6%) received more neoadjuvant therapy, but there was no difference in positive margin rates, lymph node harvest, postoperative mortality and overall survival between thoracic and non-thoracic centres. Across thoracic centres, rates of neoadjuvant therapy varied from 16.4–81.6%, positive margin rates varied from 8.2–29.6%, median lymph node harvest varied from 7–20 nodes, postoperative mortality varied from 0–18.7%, and median survival varied from 17–26 months. Conclusion: There was significant variability in treatment patterns, surgical outcomes, and survival among patients treated at designated thoracic centres. Feedback of patient outcomes to surgeons and hospitals, and translating best practices from high-performing hospitals to other hospitals, is the next step in improving outcomes.